Leakage Research of Split-type Air-conditioner using R290 as Refrigerant - 张网; 杨昭; 王婕; 吕东; 钟志锋 (Zhileng xuebao, 2013)
The ozone depletion potential (ODP) and global warming potential (GWP) of HCFCs and HFCs are higher than hydrocarbons (HCs). R290 is perfect in environmental protection and energy saving performance. In order to determine the combustible region of leaked R290 from indoor unit of air-conditioner, a test room was established in this study. The distribution of R290 concentration was studied after it leaked in the room with different room area, installation height of indoor unit, location of the leakage and different leakage rate. The results showed that combustible region is limited only in the region very close to the indoor unit, and combustible region only exists during the leakage process, which will quickly disappear once the leakage stops.